2001
DOI: 10.1063/1.1370536
|View full text |Cite
|
Sign up to set email alerts
|

High-quality porous-silicon buried waveguides

Abstract: This letter reports a method to produce porous-silicon waveguides by means of a laser local oxidation process. The estimated losses of the waveguides are below 1 dB/cm. This demonstrates the applicability of this material in integrated optics and telecommunications. Moreover, our results disclose the opportunity to integrate optoelectronic devices onto Si substrates. The laser writing method is achievable at low laser power, thus it is highly efficient and achievable with the standard equipment present in most… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
1
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 13 publications
1
48
1
1
Order By: Relevance
“…For that purpose substituting surface hydrogen by another chemical species has appeared desirable. Oxidations (Rossi et al, 2001;Bsiesy, et al 1991;Petrova-Koch et al, 1992) nitradation (Anderson et al, 1993) and halogenetion (Lauerhaas & Sailor, 1993) are found to be useful for PS surface passivation. Derivatisation by organic groups and polymer (Lees et al 2003;Mandal et al 2006), offers an alternative possibility to stabilize the material.…”
Section: Introductionmentioning
confidence: 99%
“…For that purpose substituting surface hydrogen by another chemical species has appeared desirable. Oxidations (Rossi et al, 2001;Bsiesy, et al 1991;Petrova-Koch et al, 1992) nitradation (Anderson et al, 1993) and halogenetion (Lauerhaas & Sailor, 1993) are found to be useful for PS surface passivation. Derivatisation by organic groups and polymer (Lees et al 2003;Mandal et al 2006), offers an alternative possibility to stabilize the material.…”
Section: Introductionmentioning
confidence: 99%
“…First of all, even if the result regarding the losses reported in Ref. [12] are impressive, the realisation of porous silicon waveguide having low losses is still a difficult task. Moreover, regarding the nonlinear optical characterization, the high pump power needed to excite nonlinear effects could damage the porous silicon.…”
Section: Resultsmentioning
confidence: 96%
“…[12], a method for the lateral definition of waveguide was presented based on laser local oxidation (LALOX). This approach demonstrated a simple and efficient way to realize buried waveguides.…”
Section: Raman Amplifier In Porous Silicon Waveguidementioning
confidence: 99%
“…The PS sample is placed on a 2D motorized stage driven by a computer, any pattern can be in principle produced. The laser direct writing process is the same as that was reported for the fabrication of nanoporous silicon waveguides [15]. Gratings with periods ranging from 3 to 7 µm were fabricated by using a continuous wave argon ion laser at the power up to 20 mW and a laser scanning speed up to 400 µm/s.…”
Section: Fabrication Of Surface-relief Diffraction Gratings and Planamentioning
confidence: 99%